2020
DOI: 10.2147/cmar.s258178
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA BLACAT1 Promotes the Tumorigenesis of Gastric Cancer by Sponging microRNA-149-5p and Targeting KIF2A</p>

Abstract: Objective: Gastric cancer (GC) is a gastrointestinal tumor. This study is aimed to explore the regulatory mechanism of long non-coding RNA BLACAT1 (BLACAT1)/microRNA-149-5p (miR-149-5p)/KIF2A cascade on GC. Methods: The expression of BLACAT1, miR-149-5p and KIF2A in GC was detected by qRT-PCR. The proliferation, migration and invasion of GC cells in vitro were analyzed by MTT, wound-healing and transwell assay, respectively. The xenograft tumor model was constructed in nude mice to confirm the inhibition effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…We next demonstrated that miR-149-5p directly bound to CCDC6 or circDNA2 via dual-luciferase reporter gene assays and functional gain and loss experiments. Several studies 20 , 34 , 35 independently reported that miR-149-5p has a tumor-suppressive role in GC, which was consistent with our findings. In our study, the AUC for a single miR-149-5p expression level to predict the risk of GC occurrence reached 0.7102, indicating that miR-149-5p has potential as a biomarker for GC diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…We next demonstrated that miR-149-5p directly bound to CCDC6 or circDNA2 via dual-luciferase reporter gene assays and functional gain and loss experiments. Several studies 20 , 34 , 35 independently reported that miR-149-5p has a tumor-suppressive role in GC, which was consistent with our findings. In our study, the AUC for a single miR-149-5p expression level to predict the risk of GC occurrence reached 0.7102, indicating that miR-149-5p has potential as a biomarker for GC diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…Mechanistically, miR-149-5p expression reduction is witnessed in GC samples, but enhancement of miR-149-5p hinders the migratory and invasive properties of tumor cells [ 30 ]. An innovative article about GC also reports that miR-149-5p is abated in tumor samples, and further unravels that up-regulated miR-149-5p has a damaging effect on the biological activities of GC cells [ 31 ]. Notably, Yang Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another study demonstrated that lncRNA BLACAT1 promotes the proliferation, migration and invasion of GC cells by regulating the miR-149-5p/KIF2A axis (50). CircNHSL1 can affect the expression of YWHAZ through sponging miR-149-5p, thereby regulating the progression of GC (51).…”
Section: Gastric Cancermentioning
confidence: 98%